2005
DOI: 10.1002/ajhb.20459
|View full text |Cite
|
Sign up to set email alerts
|

Y‐chromosome diversity is inversely associated with language affiliation in paired Austronesian‐ and Papuan‐speaking communities from Solomon Islands

Abstract: The Solomon Islands lie in the center of Island Melanesia, bordered to the north by the Bismarck Archipelago and to the south by Vanuatu. The nation's half-million inhabitants speak around 70 languages from two unrelated language groups: Austronesian, a language family widespread in the Pacific and closely related to languages spoken in Island Southeast Asia, and "East Papuan", generally defined as non-Austronesian and distantly related to the extremely diverse Papuan languages of New Guinea. Despite the archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 38 publications
(40 reference statements)
1
34
0
Order By: Relevance
“…In reconstructing the demographic history of Oceania, our results not only fill an important gap between previous genetic studies on the mainland of New Guinea in the west, 9-13 the Bismarck Archipelago in the north [14][15][16] and the Solomon Islands in the east, 17,18 but also provide further insights into how human culture impacts on human genetics.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In reconstructing the demographic history of Oceania, our results not only fill an important gap between previous genetic studies on the mainland of New Guinea in the west, 9-13 the Bismarck Archipelago in the north [14][15][16] and the Solomon Islands in the east, 17,18 but also provide further insights into how human culture impacts on human genetics.…”
Section: Introductionmentioning
confidence: 65%
“…1,2 Previous studies have addressed human genetic variation in Oceania, particularly Polynesia, [3][4][5][6][7][8] mainland New Guinea [9][10][11][12][13] and Island Melanesia. [14][15][16][17][18] One area of Near Oceania (NO) yet understudied from a human genetic perspective is the island region off the southeastern tip of New Guinea (Figure 1). Administratively designated the Milne Bay Province of Papua New Guinea (PNG), this area encompasses the D'Entrecasteaux Islands (ie, Normanby, Fergusson, Dobu and Goodenough), the Trobriand Islands, the Woodlark group (ie, Gawa, Woodlark and the Laughlan Islands), the Louisiade Archipelago (ie, Misima, Sudest, Rossel and the islands of the Calvados chain), as well as a portion of the nearby PNG mainland.…”
Section: Introductionmentioning
confidence: 99%
“…1 A) (7,9,10). These processes, which occur when migrating farmers meet resident hunter-gatherers face to face, likely characterize the expansion of Austronesian speakers into regions that were long occupied by indigenous populations in eastern Indonesia and New Guinea (7,11,12). However, most language-gene studies have sampled at a geographic scale, which is too coarse to permit any refined inference about the dynamics of language change in these contact zones.…”
mentioning
confidence: 99%
“…It will be shown that the set of relationships shown by the linguistic structural data is plausible from a geographic perspective, and that non-phylogenetic accounts of the geographic pattern fit the data poorly. This analysis has also proved useful in the generation of testable hypotheses, particularly in the realm of human genetics (e.g., Cox and Lahr, 2006;Hunley et al, 2007).…”
Section: Phylogenetic Analysismentioning
confidence: 99%